Impact of service effectiveness and telemedicine use on patient satisfaction using telemedicine X hospital, Semarang City in Covid-19 pandemic - Nadiya Arawinda Andar; Yuliani Setyaningsih; Luky Dwiantoro (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Since the outbreak of Corona Virus Disease (COVID-19), face-to-face services were initially limited, and communication between doctors and patients during a pandemic was less effective, so health services changed. Telemedicine, which was initially only communication between hospital departments or between hospitals, has become all kinds of communication, such as patient-doctor, patient-nurse, patient-pharmacy and so on, using Telemedicine. The use of telemedicine services is one of the strategies to prevent the spread of COVID-19 because Telemedicine provides health services using electronic communication technology. Patients and medical personnel do not need to meet in person in one place but still communicate through the application. Patient satisfaction in using Telemedicine is a crucial and vital indicator that needs to be considered to improve the quality of telemedicine medical services.Objectives: To analyze the relationship between the effectiveness of services and the use of Telemedicine on patient satisfaction using Telemedicine.Methods: Quantitative with a retrospective descriptive research design. Data was collected using an online questionnaire for 350 patients at Hospital X in Semarang City. Patients who met the inclusion and exclusion criteria were taken by purposive sampling. The analysis of this study included univariate, bivariate, and multivariate analyses. The chi-square test and logistic regression were used in this study.Results: Regarding the effectiveness of the service and use of Telemedicine, most respondents rated the service's effectiveness as good, 139 (92,1%) of respondents, and the majority of respondents considered the use of Telemedicine to support as many as 136 (90,1%) of respondents. Patient satisfaction showed that most respondents were satisfied, as many as 140 (92,7%) respondents. The relationship between service effectiveness and patient satisfaction demonstrates that the service effectiveness variable is significantly related to patient satisfaction (p-value = 0,006 ≤ Level of Significant = 0,05). The relationship between telemedicine use and patient satisfaction shows that telemedicine use has a significant relationship with patient satisfaction (p-value = 0,014 ≤ Level of Significant = 0,05).Conclusion: most of the respondents rated the effectiveness of the service as good, most of the respondents supported the use of Telemedicine, most of the respondents were satisfied, and the variable of service effectiveness was significantly related to patient satisfaction.